Effective combination of bone substitute and screws in the jail technique: a biomechanical study of tibial depression fractures - Doht, Stefanie (Springer-Verlag, 2012)
PURPOSE: The aim of this study was to investigate a new drillable calcium phosphate cement (Norian drillable Synthes GmbH) as a bone substitute either alone or in combination with screws in the jail technique (Petersen et al. Unfallchirurg Mar 109(3):219–234, 2006; Petersen et al. Unfallchirurg Mar 109(3):235–244, 2006) with regard to the primary stability in lateral tibial depression fractures. METHODS: Lateral depression fractures of the tibial plateau were created in a biomechanical fracture model. After reduction they were stabilised with bone substitute (group one), bone substitute with additional four screws in the jail technique (group two) or four screws only (group three). Displacement under cyclic loading, stiffness and maximum load in load-to-failure tests were determined. RESULTS: The groups with the bone substitute showed a lower displacement of the depressed articular fragment under cyclical loading and a higher stiffness. The maximum load was higher for the groups with screws. CONCLUSIONS: Only the combination of bone substitute and screws prevented secondary loss of reduction and, at the same time, provided enough stability under maximum load.